2019
DOI: 10.11648/j.ajns.20190802.13
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Cyberloafing and Its Relationship to Procrastination and Conscientiousness in Damanhour National Medical Institute

Abstract: Cyber-loafing involves an unproductive use of time in the workplace and distracts employees from their responsibilities and duties. This study was conducted because there is a risk posed on patient's safety if nurses are cyberloafing and if this behavior has a direct relation with procrastination and lack of conscientiousness. Aim of the study: to determine the relationship between cyberloafing, procrastination and conscientiousness among staff nurses working in Damanhour National Medical Institute. Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The findings revealed that nurses in Saudi Arabia exhibited low levels of minor and serious CB. This finding was consistent with previous studies in different countries among nurses (Arslan & Demir, 2016; Kemer & Özcan, 2021; Zein El Din & Baddar, 2019), business employees (Blanchard & Henle, 2008; Stoddart, 2016) and public workers (Çınar & Karcıoğlu, 2015). In addition, it was found that nurses engaged in minor CB more frequently than serious CB, which was supported by previous studies that reported similar findings among nurses (Arslan & Demir, 2016; Kemer & Özcan, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that nurses in Saudi Arabia exhibited low levels of minor and serious CB. This finding was consistent with previous studies in different countries among nurses (Arslan & Demir, 2016; Kemer & Özcan, 2021; Zein El Din & Baddar, 2019), business employees (Blanchard & Henle, 2008; Stoddart, 2016) and public workers (Çınar & Karcıoğlu, 2015). In addition, it was found that nurses engaged in minor CB more frequently than serious CB, which was supported by previous studies that reported similar findings among nurses (Arslan & Demir, 2016; Kemer & Özcan, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Although the uncertainty of the exact factors affecting cyberloafing behavior remains valid, there are studies indicating that cyberloafing behavior is common regardless of profession, working hours, or even age and gender [ 21 ]. Jiang et al (2020) developed a theoretical model to understand under which conditions the use of personal technology in the workplace can increase or decrease the job performance of the employee.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies, it has been emphasized that cyberloafing may cause economic losses by reducing productivity due to ineffective use of time and resources in the workplace, alienation from work, procrastination, decreased productivity, decreased organizational/individual performance, technology addiction and patient safety [ 1 , 26 – 29 ]. Furthermore, the detrimental effects of cyberloafing on organizational trust, organizational justice and work engagement have been empirically validated [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since information and communication technologies (ICT) are developing rapidly in today’s world, many organizations are committed to digital transformation [ 1 ]. In health care industry, ICT is widely used in the field of nursing [ 2 ]. When nurses provide medical services, they make extensive use of Internet tools to record patient data and access patient information [ 3 ].…”
Section: Introductionmentioning
confidence: 99%